2002
DOI: 10.3917/spub.024.0345
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction des patients hospitalisés à Hô Chi Minh-Ville, Viet Nam

Abstract: This study aims to describe the level of satisfaction of patients and their families, according to the type of hospital and the sociodemographic characteristics of patients hospitalised within Ho Chi Minh City (HCMC), Vietnam. The study is supported by a sample of 538 patients and their families from all of the hospitals in HCMC to whom an evaluation questionnaire was given to be filled out on the day of their release. The average age is 39, and 64.4% are women. The scores measuring the level of satisfaction v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
1
13
2
1
Order By: Relevance
“…This lengthy waiting time (more than 15 min) had a direct relationship with patient dissatisfaction in emergency department. This feature has been reported by many other studies whose included both the real stay-in-the-waiting-room time and the waiting time perceived by the patient [20-23], the latter was more predictive of satisfaction than the former [20,21]. …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This lengthy waiting time (more than 15 min) had a direct relationship with patient dissatisfaction in emergency department. This feature has been reported by many other studies whose included both the real stay-in-the-waiting-room time and the waiting time perceived by the patient [20-23], the latter was more predictive of satisfaction than the former [20,21]. …”
Section: Discussionsupporting
confidence: 73%
“…The finding of our study revealed that average time a patient waited to be seen by an emergency physician was 47.5 min. Compared with similar studies, the waiting time in our study was much more [20-23]. This lengthy waiting time (more than 15 min) had a direct relationship with patient dissatisfaction in emergency department.…”
Section: Discussioncontrasting
confidence: 62%
“…This was attributed to the lower levels of education in older patients. [25] Educational level had no impact on satisfaction in our study. Other reports from Saudi Arabia, however, indicated that the more educated the patients were, the more likely they were to be satisfied.…”
Section: Discussioncontrasting
confidence: 50%
“…This is reflected in the low rates of dissatisfied 5% in our series and 4.4% in Nguyen's in Vietnam [13].…”
Section: Discussionmentioning
confidence: 51%